Exploring Politeness Through Modality: A Corpus-Based Analysis of Modal Verbs in Indonesian EFL Textbooks - Oktavianti, Ikmi Nur; Dewantara, Enggar Bagas; Radzuan, Noor Raha Mohd; Fauzi, Wan Jumani Binti (JOLLT Journal of Languages and Language Teaching, 2026)
Politeness is a core aspect of language use and is frequently realized through modality, particularly modal verbs expressing permission and indirectness. In EFL contexts, textbooks play a crucial role in shaping learners’ pragmatic competence by modeling how modal verbs encode culturally appropriate politeness strategies. This study aims to explore modal verbs expressing politeness in English textbooks for grades 10, 11, and 12. A corpus-assisted approach was employed and the primary data consisted of reading and instructional texts from the three English textbooks constructed as a corpus. The texts were converted into txt format and processed using AntConc to analyze six modal verbs associated with politeness: may, might, can, could, will, and would. The analysis focused on frequency counts and contextual usage identification to determine how each modal conveyed politeness in different topics and tasks. The results showed an increasing frequency of modal verbs across grade levels, with 183 occurrences in Grade 10, 329 in Grade 11, and 343 in Grade 12. Across all grades, the modal verb can was the most frequently used, while modal verbs might and could were rarely used. Modal verbs like may, can, might, could, will, and would in the textbooks reflect Indonesian social norms of politeness. Among them, modal verbs can, will, and may are used most often, showing common expressions of permission and polite requests in formal and everyday contexts. The findings suggest that modal verb usage in the textbooks reflects Indonesian cultural values, particularly the preference for polite, indirect communication in formal and educational settings.